2017
DOI: 10.1021/acs.langmuir.7b02491
|View full text |Cite
|
Sign up to set email alerts
|

What Governs Friction of Silicon Oxide in Humid Environment: Contact Area between Solids, Water Meniscus around the Contact, or Water Layer Structure?

Abstract: In order to understand the interfacial parameters governing the friction force (F) between silicon oxide surfaces in humid environment, the sliding speed (v) and relative humidity (RH) dependences of F were measured for a silica sphere (1 μm radius) sliding on a silicon oxide (SiO) surface, using atomic force microscopy (AFM), and analyzed with a mathematical model describing interfacial contacts under a dynamic condition. Generally, F decreases logarithmically with increasing v to a cutoff value below which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…The variations in adhesion as a function of surface wettability obey the model in Equation 3. Many research groups have shown the possibility of controlling interfacial adhesion by adjusting the wettability of a surface [91][92][93]. As shown in Figure 12, upon either nor p-type doping with subsurface polyelectrolytes, graphene surfaces become more hydrophilic [59], water adsorption is enhanced, and F a (i.e., the pull-off force) increases significantly.…”
Section: Effect Of Water Condensation On Capillary Forcementioning
confidence: 99%
See 4 more Smart Citations
“…The variations in adhesion as a function of surface wettability obey the model in Equation 3. Many research groups have shown the possibility of controlling interfacial adhesion by adjusting the wettability of a surface [91][92][93]. As shown in Figure 12, upon either nor p-type doping with subsurface polyelectrolytes, graphene surfaces become more hydrophilic [59], water adsorption is enhanced, and F a (i.e., the pull-off force) increases significantly.…”
Section: Effect Of Water Condensation On Capillary Forcementioning
confidence: 99%
“…In this case, the sliding interface can be modeled by a single-asperity contact if the elastic deformation of the solid is larger than the topographic features of the initial surface [139,140]. As discussed in Sections 2 and 3, strongly H-bonded solid-like water can grow on hydrophilic surfaces, not only affecting F a [41] but also playing an important role in the resulting friction behavior [91].…”
Section: Effect Of Adsorbed Water Structure On Friction Force At Singmentioning
confidence: 99%
See 3 more Smart Citations